Genotypic and Phenotypic Study of Antiviral Resistance Mutations in Refractory Cytomegalovirus Infection . (22nd August 2022) - Santos Bravo, Marta; Plault, Nicolas; Sánchez-Palomino, Sonsoles; Rodríguez, Cristina; Navarro Gabriel, Mireia; Mosquera, María Mar; Fernández Avilés, Francesc; Suarez-Lledó, María; Rovira, Montserrat; Bodro, Marta; Moreno, Asunción; Linares, Laura; et al.
Abstract: Background: This study describes the genotypic and phenotypic characterization of novel human cytomegalovirus (HCMV) genetic variants of a cohort of 94 clinically resistant HCMV patients. Methods and results: Antiviral-resistant mutations were detected in the UL97, UL54, and UL56 target genes of 25 of 94 (26.6%) patients. The genotype-phenotype correlation study resolved the status of 5 uncharacterized UL54 deoxyribonucleic acid polymerase (G441S, A543V, F460S, R512C, A928T) and 2 UL56 terminase (F345L, P800L) mutations found in clinical isolates. A928T conferred high, triple resistance to ganciclovir, foscarnet, and cidofovir, and A543V had 10-fold reduced susceptibility to cidofovir. Viral growth assays showed G441S, A543V, F345L, and P800L impaired viral growth capacities compared with wild-type AD169 HCMV. Three-dimensional modeling predicted A543V and A928T phenotypes but not R512C, reinforcing the need for individual characterization of mutations by recombinant phenotyping. Conclusions: Extending mutation databases is crucial to optimize treatments and to improve the assessment of patients with resistant/refractory HCMV infection. Abstract : Genotype-phenotype correlation study resolved the status of UL54 A928T high triple-resistant mutation to ganciclovir, foscarnet, and cidofovir and UL54 A543V-resistant mutation to cidofovir found in clinical isolates. Moreover, UL54 G441S, A543V and UL56 F345L, P800L impaired viral growth capacities.